1988
DOI: 10.1016/0016-7037(88)90154-8
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, antimony and vanadium in the North Atlantic Ocean

Abstract: The presented data for As and V have extended the limited basis for comparison, so that inter-ocean fractionation processes can now be recognized. The concentrations of both As and V show regular increases in the ocean deep water as it passes from the North Atlantic (As 19.0; V 32.6 nmol I-') via the South Atlantic (As 21. I nmol I-') and Indian Ocean (As 22.5; V 35.6 nmol I-') lo the Pacific Ocean (As 24.0; V 36.4 nmol I-'). The magnitude ofbiological recycling for V and As. as deduced from interoceanic fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 35 publications
4
36
0
1
Order By: Relevance
“…present as Sb III even under oxidizing conditions since many environmental factors such as biological activity or kinetic considerations cannot be included in the simplified thermodynamic calculations ŽAndreae et al, 1981;Andreae and Froelich, 1984; . Middelberg et al, 1988;Cutter and Cutter, 1995 . Similar reasons can explain the presence of the Ž . oxidized form Sb V in reducing sediment porewa-Ž .…”
Section: Introductionmentioning
confidence: 84%
“…present as Sb III even under oxidizing conditions since many environmental factors such as biological activity or kinetic considerations cannot be included in the simplified thermodynamic calculations ŽAndreae et al, 1981;Andreae and Froelich, 1984; . Middelberg et al, 1988;Cutter and Cutter, 1995 . Similar reasons can explain the presence of the Ž . oxidized form Sb V in reducing sediment porewa-Ž .…”
Section: Introductionmentioning
confidence: 84%
“…A certain number of studies plainly ignored the conservation issue (e.g. refs [66][67][68][69]). Observations have been summarised in Table A3.…”
Section: Conservation Issuesmentioning
confidence: 99%
“…[34] Microorganisms capable of reducing vanadium have been isolated and the possibility of microbial reduction causing precipitation of V in anoxic environments has been recognised. [35] Several studies have suggested V concentrations are reduced by phytoplankton uptake or biogenic adsorption in surface layers of oceans [36,37] or lakes. [38] Observations of depletions of V in oxic waters of the Mississippi River Delta were initially attributed to these processes.…”
Section: In Situ Profilesmentioning
confidence: 99%